Feasibility and Acceptability of Engaging Significant Adults in Youth Sexual and Relationship Violence Prevention Work. (August 2022) - Banyard, Victoria; Jefferson, Gena C.; Segura, Anna; Forman, Susan G.; Haviland, Mary; McMahon, Sarah; DeSilva, Abigail R.; Frye, Victoria; Sarkar, Saswati
Relationship and sexual violence (RSV) disproportionately affect youth in immigrant and other marginalized communities yet few prevention initiatives are truly grounded in their experiences. The current study represents a pilot implementation evaluation of youth-led workshops to engage significant adults (parents, grandparents, aunts, adult siblings, community leaders) as RSV prevention partners in diverse communities in a large urban area. The current mixed methods evaluation examined the perceptions of 66 adults and six youth leaders of four, day-long adult training workshops. Results showed high feasibility and acceptability and an important role for significant adults in enhancing RSV prevention.